2009
DOI: 10.1016/j.jconrel.2009.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced intracellular delivery using arginine-rich peptides by the addition of penetration accelerating sequences (Pas)

Abstract: Cell penetrating peptides (CPPs), including arginine-rich peptides, are attractive tools for the intracellular delivery of various bioactive molecules with a low membrane permeability. We showed that the accelerated intracellular delivery of arginine-rich peptides was achieved by the addition of a short peptide segment (penetration accelerating sequence, Pas) to arginine-rich CPPs. The cytosolic release of the Pas-attached arginine-rich CPPs was observed within 5 min after the treatment of the cells with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 26 publications
6
110
0
Order By: Relevance
“…38 As demonstrated here and by others, the hydrophobic domain of the PTDM is important to protein internalization. 38,39 The block copolymer outperformed all other polymers tested at protein delivery yielding an MFI around 20 times higher, as determined by FCM (Figure 5B). This was corroborated with confocal images, which revealed both punctate and diffuse fluorescence within the imaged cells (Figure 5A).…”
Section: Resultsmentioning
confidence: 83%
“…38 As demonstrated here and by others, the hydrophobic domain of the PTDM is important to protein internalization. 38,39 The block copolymer outperformed all other polymers tested at protein delivery yielding an MFI around 20 times higher, as determined by FCM (Figure 5B). This was corroborated with confocal images, which revealed both punctate and diffuse fluorescence within the imaged cells (Figure 5A).…”
Section: Resultsmentioning
confidence: 83%
“…By the same token, both Pas-modification and N-terminal acylation of arginine-rich CPPs (PasR8 and C6R8) were developed to significantly improve delivery efficiency by raising hydrophobicity [43,46]. Studies have shown that the guanidinium-head groups of arginines were crucial for cellular uptake due to their interactions with membrane phospholipids, as substituting nitrogen of guanidine with oxygen reduced the ability of transduction [60,63].…”
Section: Discussionmentioning
confidence: 99%
“…Lo and Wang discovered that a PTD of TAT comprised of additional polyhistidine and cysteine residues possessed endosomolytic properties and increased the gene expression of DNAs carried by this CPP [42]. Takayama et al reported that a short Pas (FFLIPKG) peptide enhanced the intracellular delivery of octaarginine within 5 min, even in the presence of serum [43].…”
Section: Introductionmentioning
confidence: 99%
“…CPPs can be used in vivo to deliver their cargo to virtually all tissues [43]. Methodologies based on CPPs are constantly being improved as demonstrated by the recent characterization of penetration accelerating sequences (PAS) that significantly increase the cytosolic release of CPPs taken up by cells [44].…”
Section: Therapeutic Peptide Design Improvementmentioning
confidence: 99%